Early Juvenile Human T-cell Lymphotropic Virus Type-1-Associated Myelopathy/Tropical Spastic Paraparesis: Study of 25 Patients - Varandas, Cinthya Maria Neves (2018)
Fundação de Amparo à Pesquisa do Estado da Bahia (FAPESB) [grant number RED0028/2012 to L. F.] and Conselho Nacional de Desenvolvimento Científico e Tecnológico – CNPq [grant number 409985/2016-3 to A. L. B.].